2007
DOI: 10.1007/s10815-007-9157-2
|View full text |Cite
|
Sign up to set email alerts
|

Preimplantation sex selection demand and preferences among infertility patients in Midwestern United States

Abstract: Purpose To determine the demand and preferences of infertility patients for sex selection for nonmedical reasons, and to investigate the relation between these choices and their demographic and socioeconomic characteristics. Methods A cross-sectional, self-administered survey by mail was conducted at a University hospital-based fertility center of 1,350 consecutive women who presented for infertility care, to assess patient demand and preferences for sex selection. Results Of respondents, 49% wanted to select … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 21 publications
1
18
0
Order By: Relevance
“…23,24 Organizations such as the American College of Obstetrics and Gynecologists (ACOG) have issued statements suggesting gender selection is an inappropriate use of medical resources and perpetuates gender bias. 25 Despite this opposition the use of PGT for sex selection is legal in a diverse number of countries, including USA, Mexico, Thailand and Italy. Indeed, in these countries the use of embryo testing for sex selection is on the increase, with the Society of Assisted Reproductive Technology (SART) reporting that the use of PGT for gender selection in the USA increased from 9% of PGT cycles in 2005 to 22% in 2008.…”
Section: Key Messagementioning
confidence: 99%
“…23,24 Organizations such as the American College of Obstetrics and Gynecologists (ACOG) have issued statements suggesting gender selection is an inappropriate use of medical resources and perpetuates gender bias. 25 Despite this opposition the use of PGT for sex selection is legal in a diverse number of countries, including USA, Mexico, Thailand and Italy. Indeed, in these countries the use of embryo testing for sex selection is on the increase, with the Society of Assisted Reproductive Technology (SART) reporting that the use of PGT for gender selection in the USA increased from 9% of PGT cycles in 2005 to 22% in 2008.…”
Section: Key Messagementioning
confidence: 99%
“…In an attempt to evaluate possible demographic and social implications for the balance between sexes in the event of freer and greater use of existing technologies, many studies around the world deal with the identification and analysis of trends in favoring the sex of offspring [ 1 , 18 , 23 25 ] and note obstetric and socioeconomic background variables as being associated with it. Regarding the former, about one-fifth of the applicants in the present study would have had to undergo IVF for other medical reasons, and might have expected this to enable their eligibility, but this did not guarantee approval of PGD.…”
Section: Discussionmentioning
confidence: 99%
“…Family size and composition have been considered a major motivator for sex-selection. Many studies, including studies in Israel [ 28 , 29 ], have indicated that in families where there are children of a single sex, and especially in cases of at least three of the same sex, there is clear preference for the other sex [ 1 , 23 25 , 30 , 31 ] The association between family composition and preference for offspring’s sex is not surprising given the ongoing trend of declining total fertility rate in Western countries [ 32 ], as well as in Israel [ 33 ]. An Israeli study regarding attitudes towards PGD included a survey among a population of married couples of reproductive age who were parents to at least two children of only one sex [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was widely assumed that the male, via his sperm, was solely responsible for the characteristics of the resulting child, and women were valued predominantly for their ability to deliver children, specifically, male children. In contrast, an American study found that patients undergoing fertility treatment expressed a slight preference for female offspring . One must be careful, nonetheless, to realize that the pursuit of information regarding fertility and the fetus is often not benign, being entrenched in a system of female oppression and marginalization.…”
Section: Case Studies: Reproductive Autonomy In Selected Contextsmentioning
confidence: 98%